2019
DOI: 10.1007/s40093-019-0251-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biochar and nitrogen fertilizer on soil physicochemical properties, nitrogen use efficiency and upland rice (Oryza sativa) yield grown on an Alfisol in Southwestern Nigeria

Abstract: Purpose Biochar and inorganic fertilizer when co-applied have been reported to increase crop yield and enhance soil fertility. However, studies on this complementary effect on soil properties and rain-fed upland rice performance in Sub-Saharan Africa are still scanty. Methods Field factorial studies conducted over 2 years was set up to investigate the interactions between rice husk biochar and inorganic nitrogen (N) fertilizer on a sandy clay loam Alfisol. A two-factor (4 × 4) in RCBD where rice husk biochar w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 53 publications
2
26
2
1
Order By: Relevance
“…Our results showed that when biochar application rate was too high as the case with P48 treatment, the 15 N uptake in most organs (Figure 4a) and the overall 15 N utilization efficiency of maize (Figure 4b) were markedly lower than that in P12 and P24, which is in accordance with the results obtained by Oladele et al. (2019). This is because higher biochar application rates markedly improve SOC content in a short period of time (Section 3.1), as also reported in Zhang, et al (2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results showed that when biochar application rate was too high as the case with P48 treatment, the 15 N uptake in most organs (Figure 4a) and the overall 15 N utilization efficiency of maize (Figure 4b) were markedly lower than that in P12 and P24, which is in accordance with the results obtained by Oladele et al. (2019). This is because higher biochar application rates markedly improve SOC content in a short period of time (Section 3.1), as also reported in Zhang, et al (2020).…”
Section: Discussionsupporting
confidence: 91%
“…This is because biochar application improved soil physical conditions (Figure 1), availability of soil nutrient (Table 1) and N uptake by maize plant (Figures 3 and 4). Improvement of soil properties and nutrient uptake by plants after biochar application has been shown to increase crop yield (Mandal et al., 2016; Oladele et al., 2019; Wang et al., 2020). However, excessive biochar application (P48 treatment) appeared to slightly reduce the N uptake and absorption by maize plant parts (Figure 4), resulting in the slight decline in crop yield and biomass in each plant parts (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that IPNS treatments had no significant effect on soil bulk density in acidic soil, although IPNS treatments significantly decreased soil bulk density in charland soil. Many studies have shown that including organic material in the soil reduces its bulk density [75,76]. The reason for the decreased soil bulk density is the addition of organic materials, which increases soil organic matter content, resulting in soils that are more friable, porous, and chemically active, reducing soil bulk density [77].…”
Section: Effect Of Ipns On Soil Physicochemical Propertiesmentioning
confidence: 99%
“…The interaction between biochar and N has shown to increased plant growth. It attributed that biochar can increase the availability of nutrients, especially N for plants (Oladele et al, 2019). N was released slowly, so that is utilized by the plants (Haider et al, 2016).…”
Section: Estimated Response For Maize Variables Of Experimental Factorsmentioning
confidence: 99%